Sejarah Perkembangan Hukum Pidana di Indonesia: Menyongsong Kehadiran KUHP 2023 dengan Memahami dari Aspek Kesejarahan - Mubarok, Nafi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2024)
According to von Savigny, the study of history in law has urgent value regarding legal continuity in the past, present and future. Of course, this also applies to the history of Indonesian criminal law, which has entered a new phase with the enactment of Law Number 1 of 2023 concerning the Criminal Code. This article aims to understand the historical aspect of the formation of the 2023 Criminal Code, which is more broadly related to the history of the development of criminal law in Indonesia. At the end of the article, it is concluded that the periodization of the development of criminal law in Indonesia can be divided into six stages, namely: (1) the Nusantara kingdom period, (2) the VOC colonial period, (3) the Dutch colonial period, (4) the Japanese colonial period, (5) the period after independence, and (6) the period for the formation of the 2023 Criminal Code. The period for the formation of the 2023 Criminal Code can be explained by characterizing: (1) efforts to realize the ideals of Indonesian law, or volkgeist (spirit of the people), (2) that the Criminal Code is a recodification after decodification, and (3) recognition of customary law as "local wisdom".